Lo sguardo attraverso il mito - Prosenc, Irena (Ars et humanitas, 2015)
The paper analyses the figure of the poet in two works by the contemporary Italian writer Claudio Magris: in the short prose text Lei dunque capira (You Will Therefore Understand) and the novel Alla cieca (Blindly). In both works the figure of the poet is constructed through the eyes of the other as well as through the prism of mythological narration. In Lei dunque capira, the image of the poet is shaped by Eurydice's voice, which filters the Orpheus myth, actualising and perhaps banalizing it. The novel, on the other hand, uses the Argonauts myth, intertwined with the Odysseus and Orpheus myths, to reflect on the nature of the narrating voice. The novel questions whether autobiographical narration can at all be reliable or whether it is to be considered - along with mythological narration - as nothing more than "réclame", representing a deformed view of personal, historical and mythological memory. Magris questions the existence of a stable narrative voice in contemporary fiction, since it appears fragmented and unsure about its own identity. Both works include myth as the central element facilitating reflection on fundamental metaliterary issues. "Looking at the Myth" thus becomes "looking through the myth", as well as, in Eurydice's narration, looking at a reflection: "I haven't seen myself, I do not know myself. But if you tell me about this, I shall know it and will be able to narrate it."
Keywords: Argonauts; Argonavti; figure of the poet; italian literature; italijanska književnost; lik pesnika; literarne študije; Magris; Magris, Claudio; miti; mythology; myths; narrator; Orfej; pripovedovalec